Pengaruh Price Perception, Discount, Dan Customer Experience Terhadap Customer Loyalty (Studi Pada Pelanggan Di Toko Basmalah Kecamatan Ranuyoso Kabupaten Lumajang) - Gufron, Muhamad Riyanto; Salim, Muhammad Agus; Rahman, Fahrurrozi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to examine the effect of price perception, discount, and customer experience on customer loyalty among customers of Toko Basmalah in Ranuyoso District, Lumajang Regency. The background of this research is based on the importance of building customer loyalty amid the intense competition in the retail industry. The research employs a quantitative approach with an explanatory research type. The sample consists of 108 respondents selected using purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS. The results show that price perception, discount, and customer experience simultaneously have a significant effect on customer loyalty. Partially, each of the three variables also has a positive and significant influence on customer loyalty. These findings indicate that customer experience is the most dominant factor in building customer loyalty at Toko Basmalah. Keywords: Price Perception, Discount, Customer Experience, Customer Loyalty